Pengaruh Intervensi Mindfulness dan Berdzikir terhadap Kecemasan pada Keluarga Pendamping Pasien Tahap Terminal di Ruang ICU - Kukuh Feri Setyawan; Mohammad Arifin Noor; Indah Sri Wahyuningsih (Vitalitas Medis : Jurnal Kesehatan dan Kedokteran, 2025)
Families of terminal patients often experience anxiety triggered by the deterioration of the patient’s condition, limited information received, and feelings of loss due to facing separation from their loved ones in a critical situation. This anxiety may occur at varying levels, ranging from mild to panic, and if not properly managed, it can affect the psychological well-being of family members as well as their ability to support the patient. Therefore, appropriate interventions are needed to help reduce the psychological burden of families. One approach that can be applied is mindfulness combined with dhikr, which integrates full awareness with spiritual practice to calm thoughts and emotions. This study employed a quasi-experimental design with a one-group pretest–posttest approach without a control group, involving 20 respondents who were family members accompanying terminal patients in the ICU. Respondents were selected using total sampling according to the inclusion criteria. The research instrument consisted of an anxiety observation questionnaire, and data were analyzed using the Wilcoxon test. The results showed that before the intervention, all respondents experienced anxiety at different levels. After the intervention, there was a significant reduction, with 14 respondents (70%) in the mild anxiety category and 6 respondents (30%) reporting no anxiety. The Wilcoxon test yielded a p-value of 0.000 (<0.05), indicating a statistically significant difference between pre- and post-intervention. In conclusion, mindfulness and dhikr interventions were effective in reducing anxiety among family members accompanying terminal patients in the ICU. This method can be recommended as a spiritually based psychological support strategy to help families cope with critical situations more calmly and adaptively.